On the distinct molecular architectures of dipping- and spray-LbL films containing lipid vesicles - Aoki, Pedro H. B. [UNESP]; Alessio, Priscila [UNESP]; Volpati, Diogo; Paulovich, Fernando V.; Riul, Antonio; Oliveira, Osvaldo N.; Constantino, Carlos J. L. [UNESP] (Elsevier B.V., 2014)
The introduction of spraying procedures to fabricate layer-by-layer (LbL) films has brought new possibilities for the control of molecular architectures and for making the LbL technique compliant with industrial processes. In this study we show that significantly distinct architectures are produced for dipping and spray-LbL films of the same components, which included DODAB/DPPG vesicles. The films differed notably in their thickness and stratified nature. The electrical response of the two types of films to aqueous solutions containing etythrosin was also different. With multidimensional projections we showed that the impedance for the DODAB/DPPG spray-LbL film is more sensitive to changes in concentration, being therefore more promising as sensing units. Furthermore, with surface-enhanced Raman scattering (SEES) we could ascribe the high sensitivity of the LbL films to adsorption of elythrosin. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Layer-by-layer films; Molecular architecture; Sensing; Information visualization; Erythrosin